The Possibility of Supplementing The Listening Comprehension Components of Foreign Language Examinations with Audio Visual Tasks - Kövér, Ármin (Working Papers in Language Pedagogy, 2020)
Due to the rapid nature of technological development, the array of language learning opportunities and tools has widened. To keep up with the changing trends in language learning, language testing also has to constantly improve its practices. In real-life language use the consumption of audio-visual material is growing. Consequently, language testing professionals might also want to consider including audio-visual materials in the listening comprehension component of foreign language examinations. The topic of using audio-visual material in listening tests has already been researched before (e.g., Kellerman, 1990; Ockey, 2007; Sueyoshi & Hardison, 2005), however, these studies arrived at contradictory results. For this reason, the present study investigates the audio-only and audio-visual text comprehension of 140 language learners at four language proficiency levels (i.e., A2-C1) in two languages (i.e., English and German). The participants of the study filled in both a paper-based and a computer-based test including both audio-only and audio-visual tasks. In addition, at the end of the tests, they were asked to fill in a questionnaire regarding the usefulness of the visual input in solving the tasks. The results suggest that the inclusion of audio-visual tasks into the listening comprehension component of language tests is possible, but it requires a sound methodological rationale.